Inclusive education or school revolution (Journal of Parents and Teachers, 2014)
The Educational Reforms of Europe put special emphasis on inclusive education, which, far from being a passing educational trend, is a necessity. However, like every revolution, it demands a structural, organizational, pedagogical and methodological change. The article also describes the characteristics of a teacher and an inclusive class.
Keywords: Inclusive Education; equal opportunities; revolution; pedagogical change; methodological change.